ISU DAN MASALAH AKIDAH DAN SYARIAH DALAM PENGUBATAN SPIRITUAL ISLAM DI KALANGAN MASYARAKAT ISLAM DI MALAYSIA - Ahmad Najaa' Mokhtar; Jahid Hj Sidek; Muhammad Khairi Mahyuddin; Abdul Rahim Zumrah; Mahyuddin Ismail; Rosidayu Sabran; Mohd Rumaizuddin Ghazali (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
The spiritual Islamic medical has a significant contribution to the Muslim community. It was regarded as a basic for Islamic medical. It has been introduced by the prophet Muhammad SAW, which implemented till now by the Islamic scholars. The Muslim community were interested with this approach. However, there are still ambiguity among them in regard to originality of the spiritual Islamic medical. Therefore, this study was conducted to explore this issue in the context of Malaysia. In specific, this study examine the relationship between akidah, sharia and Islamic medical. In addition, this study was conducted to investigate the implementation of Islamic medical, in order to decrease the ambiguity among the society toward the Islamic medical. To achieve the objectives of this study, a case study was conducted. This study reveals that the ambiguity among the society toward the Islamic medical is because of miss understanding in akidah and sharia. Another reason is because the Islamic medical practitioners not emphasize on akidah and sharia during the implementation of Islamic medical.